2013
DOI: 10.1007/s00223-013-9771-1
|View full text |Cite
|
Sign up to set email alerts
|

The Long Bone Deformity of Osteogenesis Imperfecta III: Analysis of Structural Changes Carried Out with Scanning Electron Microscopic Morphometry

Abstract: The wedges of the mid-diaphyseal osteotomies carried out to correct the femoral and/or tibial native deformity in type III osteogenesis imperfecta (OI III) were used to study the remodeling patterns and lamellar organization at the level of the major deformity. Histology and scanning electron microscopy (SEM) morphology showed abnormal cortical remodeling characterized by the failure to form a cylinder of compact bone with a regular marrow canal. Atypical, flattened, and large resorption lacunae with a wide re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…Further investigation by high-resolution computed tomography confirmed the presence of unusually high vascular porosity, on average 21%, within long bone diaphyseal cortex of children with OI, when compared with control specimens from children with no known musculoskeletal disease, for which the average porosity was 3% [39]. A similar finding was since then reported by another group in a scanning electron microscopy study of mid-diaphyseal osteotomy specimens from children with OI type III, which described the presence of “flattened and elongated lacunar spaces” within regions of bone “normally taken up by compact cortex” [40]. The current study builds upon our group’s recent work, and offers an in-depth analysis of relationships between cortical tissue architecture, including vascular porosity, and the mechanical properties of diaphyseal bone in children with OI.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…Further investigation by high-resolution computed tomography confirmed the presence of unusually high vascular porosity, on average 21%, within long bone diaphyseal cortex of children with OI, when compared with control specimens from children with no known musculoskeletal disease, for which the average porosity was 3% [39]. A similar finding was since then reported by another group in a scanning electron microscopy study of mid-diaphyseal osteotomy specimens from children with OI type III, which described the presence of “flattened and elongated lacunar spaces” within regions of bone “normally taken up by compact cortex” [40]. The current study builds upon our group’s recent work, and offers an in-depth analysis of relationships between cortical tissue architecture, including vascular porosity, and the mechanical properties of diaphyseal bone in children with OI.…”
Section: Introductionsupporting
confidence: 64%
“…Low bone mass is a characteristic clinical feature of OI, and evidence of a discontinuous and porous cortical bone structure within the iliac crest and long bone diaphyses can be found in other reports [12, 13, 40, 43]. In a recent study, elevated cortex porosity observed within long bone diaphyses of children with OI was attributed to abnormal secondary remodeling, resulting in a combination of regular concentric osteons and large, flattened resorption spaces formed by drifting osteons [40]. …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Deficits of C1 can lead to numerous negative outcomes, from cosmetic blemishes such as wrinkles and decreased ability of wound healing, to life altering and debilitating diseases, such as Osteogenesis Imperfecta and Ehler– Danlos Syndrome. 6,23,33 These deficits can be caused by congenital defects, infection, autoimmune diseases, nutrient deficiency, sun damage, or old age. 4,20,26 Aging alone can reduce the collagen content of adult human skin to 1% per unit area per year.…”
Section: Introductionmentioning
confidence: 99%
“…Type III ( OMIM #259420 ) is a severe form with obvious bony deformities and reduced BMD [17]. Whereas type I OI patients have a reduced amount of type I collagen, patients with types II, III and IV ( OMIM #166220 ) have lower quality type I collagen [9,18]. Some children with OI do not fall clearly into one of these four types.…”
Section: Introductionmentioning
confidence: 99%